Farming as financial asset : global finance and the making of institutional landscapes - Ouma, Stefan (Economic transformations (Newcastle upon Tyne, England), 2020)
Since the global financial crisis, the world has seen a stark rise in financial investment in farming and agricultural production. Indeed, finance has been identified as one of the main causes of the so-called "global land rush". Agriculture and land represent safe investment opportunities and in a world with a growing population that needs to be fed, the returns are a safe bet. The debate that this has caused in the media is frequently alarmist and financiers are blamed for rising land prices and intensification of land commodification across the globe.0Stefan Ouma seeks to debunk the misconceptions and assumptions about "finance-gone-farming" with a penetrating analysis of case studies taken from both the developed and developing world, revealing the role of global finance in the agricultural sectors of these very different settings. The book provides a fascinating insight into the inner workings of the agri-focused asset management industry.